TECHNO-ECONOMIC FEASIBILITY STUDY OF BIOETHANOL PRODUCTION FROM A COMBINED CELLULOSE AND SUGAR FEEDSTOCK IN NIGERIA: 2-ECONOMIC ANALYSIS (Nigerian Journal of Technology, 2018)
The use of bioethanol in internal combustion engines is a potential green alternative to fossil fuel. Therefore, there is a need to encourage private and government investments in bioethanol production. Here, the techno-economic feasibility of establishing a 148 million liters/annum sugarcane-based bioethanol plant in Nigeria has been studied in order to motivate investors. It was undertaken with the aid of computational software (MATLAB R2017a and Excel 2016). The study shows that the plant will yield a benefit/cost ratio, net present worth, payback period and return on investment value(s) of 1.46, $ 4.29 million, 10 years and 8 % respectively, which suggests that the proposed plant would be economically feasible and profitable in Nigeria, based on the conditions adopted for the study. http://dx.doi.org/10.4314/njt.v37i4.9